2017
DOI: 10.22438/jeb/38/6/mrn-371
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a landfill leachate recirculation treatment system using quadric model

Abstract: Aim :Methodology : Results :Interpretation :The present research was carried out to study the effects of recirculation of leachate in cylindrical shaped anaerobic bioreactor on treatment of leachate as well as stabilization of municipal solid waste. Quadric and regression model were used to study the behavior of operating parameters over time scale and on COD, respectively.19 kg of solid waste was filled and compacted and in reactor and water was added to it till 20 liters of leachate prepared. The whole unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The greater COD and BOD5 increments in Br2 indicate the effect that LR has on initial waste degradation stages, as has been observed in similar studies with EW [45,46]. LR could have accelerated hydrolysis and acidogenesis processes in Br2 by favouring greater leaching of soluble organic substances from the solid waste to the liquid phase which, when recirculated, improves the contact between biomass and the more easily assimilable waste fractions [19]. This, together with the variable biodegradability characteristics of the various materials found in MWS, might explain the fluctuation in BOD/COD observed.…”
Section: Leachatesupporting
confidence: 63%
See 2 more Smart Citations
“…The greater COD and BOD5 increments in Br2 indicate the effect that LR has on initial waste degradation stages, as has been observed in similar studies with EW [45,46]. LR could have accelerated hydrolysis and acidogenesis processes in Br2 by favouring greater leaching of soluble organic substances from the solid waste to the liquid phase which, when recirculated, improves the contact between biomass and the more easily assimilable waste fractions [19]. This, together with the variable biodegradability characteristics of the various materials found in MWS, might explain the fluctuation in BOD/COD observed.…”
Section: Leachatesupporting
confidence: 63%
“…The limited applications of SSL in DC evidence the need to investigate its applicability by considering the type of waste disposed of and landfill operating conditions in these countries. Previous studies, conducted mainly with fresh waste (FW) from landfills of the organic fraction of MSW, have denoted the positive effect of LR on biogas production and parameters used as stabilisation indicators for landfills, such as volatile solids (VS), biochemical oxygen demand (BOD) and chemical oxygen demand (COD) [19][20][21][22]. Additionally, several studies in DC have reported a positive effect of LR on landfill settlement [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two times model and regression model were used to study the variation of operating parameters with time and influence on COD, and the physical and chemical characterization of leachate and solid waste was carried out by standard analysis method. Through experiments, it was proved that most of the organic and inorganic pollutants in the leachate decreased with time, and the alkalinity increased, which indicated the leachate cycle bioreactor has excellent performance, but this method is more complex and difficult to implement (Lohchab and Singh, 2017). Under anaerobic condition, the collected leachate was recycled in a cylindrical bioreactor using domestic solid waste as raw material, and various parameters of leachate collected from outlet were analyzed.…”
Section: Introductionmentioning
confidence: 99%